Giant Magnetoresistance of the Electrodeposited FeCoCu/Cu Multilayers: Metal Oxide Formation with NaOH in the Electrolyte - Tekgüla, A.; Şahin, T.; Köçkar, H.; Alper, M. (Acta Physica Polonica A, 2023)
FeCo(CoO)Cu/Cu multilayers were prepared from the electrolytes containing various amounts of NaOH by the electrochemical deposition technique. The current density decreases with the increasing molarity of NaOH in the electrolyte. Therefore, the magnetic layers deposit more slowly on the Cu layers. This may cause the oxidation of the magnetic elements. The structural analysis was performed by the X-ray diffraction technique, and the refined patterns exhibit that the multilayers have a face-centered-cubic crystal structure (Fm-3m space group). The magnetic hysteresis curves were measured by the vibrational sample magnetometers at room temperature. The saturation magnetization of the multilayers was found to be 53.02, 24.83, and 24.26 A m2/kg as a function of the NaOH amount in the electrolyte. Magnetoresistance values were measured and observed to change from 16 to 2.5% when the NaOH amount increased from 0.01 to 0.02 M in the electrolyte, and the 7% anisotropic magnetoresistance was obtained for 0.01 M NaOH. The results indicate that the NaOH may cause the occurrence of metal oxide in the magnetic layers for the multilayers produced from the electrolyte with 0.02 and 0.04 M NaOH, and this metal oxide is CoO since its crystal structure is similar to the Co, Fe, and Cu, and also, the magnetization drastically decreases with increasing NaOH amount.